Pengaruh Capital Adequacy Ratio dan Net Interest Margin terhadap Return Saham pada Perusahaan Perbankan Bank Umum Milik Negara yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2018-2023 - Jamila H. Rauf; Raflin Hinelo; Idham Masri Ishak (Economic Reviews Journal, 2025)
This study aims to analyze the relationship between the Capital Adequacy Ratio (CAR) and Net Interest Margin (NIM) on stock returns in State-Owned Commercial Banks (BUMN Banks) listed on the Indonesia Stock Exchange (IDX) for the 2018-2023 period. The Sampling technique used in this study was total sampling, where all population members were included as samples, totaling four banking companies. Data collection was based on secondary data from the financial reports published by the state-owned commercial banks listed on the IDX. The analysis employed multiple linear regression using SPSS 25 software. The results of the study indicate that, partially, the Capital Adequacy Ratio has a positive and significant effect on returns, while the Net Interest Margin has a partial negative and insignificant effect on stock returns. Simultaneously, the Capital Adequacy Ratio and Net Interest Margin influence stock returns. This is evident from the adjusted R-squared coefisient, which shows that the independent variables explain 34.6% of the variation in stock returns, while the remaining 65,4% is explained by other variables not included in the regression model.